New manganese hexaboride: stability and mechanical properties - Сагатов, Нурсултан; Sagatova, Dinara (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2025)
Through ab initio evolutionary crystal structure prediction, we have discovered a novel monoclinic phase of manganese hexaboride (MnB6) with the space group P2/m. This new polymorph is energetically favorable over the previously known hexagonal Pm2 structure at pressures below 58 GPa. Although metastable with respect to decomposition into MnB4 and B, the P2/m phase is demonstrated to be dynamically and mechanically stable at ambient pressure, as confirmed by the absence of imaginary phonon modes and the satisfaction of the Born stability criteria. Calculations of the elastic properties reveal that MnB6-P2/m is a hard, brittle material with a high Vickers hardness of 33 GPa, which surpasses that of common industrial ceramics like tungsten carbide and silicon carbide. Its bulk modulus (273 GPa), shear modulus (220 GPa), and Young modulus (519 GPa) indicate superior resistance to elastic deformation. The compound exhibits significant elastic anisotropy, as visualized by the directional dependence of its moduli and hardness. These properties establish the new MnB6-P2/m polymorph as a promising candidate for experimental synthesis and potential application as a hard material.